The influence of socio-economic status on mothers' volubility and responsiveness in a monolingual Dutch-speaking sample. Issue 2 (April 2016) - Vanormelingen, Liesbeth; Gillis, Steven
This article investigates the amount of input and the quality of mother–child interactions in mothers who differ in socio-economic status (SES): mid-to-high SES (mhSES) and low SES. The amount of input was measured as the number of utterances per hour, the total duration of speech per hour and the number of turns per hour. The quality of the mother–child interactions was analysed using a simple coding scheme: (1) response or not?, (2) incorporation or not? and (3) exact repetition or expansion? Main results showed that mothers of lowSES have fewer utterances per hour, shorter durations of speech and fewer turns per hour than mothers of mhSES. Also, lowSES mothers respond significantly less to their children's utterances and use more exact repetitions than expansions.